2011
DOI: 10.1038/onc.2011.366
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin receptor contributes to melanoma cell survival in vivo

Abstract: Erythropoietin (Epo) is widely used clinically to treat anemia associated with various clinical conditions including cancer. Data from several clinical trials suggest significant adverse effect of Epo treatment on cancer patient survival. However, controversy exists whether erythropoietin receptor (EpoR) is functional in cancer cells. In this study, we demonstrated that EpoR mRNA expression was detectable in 90.1% of 65 melanoma cell lines, and increased copy number of the Epo and EpoR loci occurred in 30% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
2
43
1
Order By: Relevance
“…Epo is a pleiotropic cytokine that regulates erythropoiesis, angiogenesis, cytoprotection, and proliferation (Foley, 2008; Glaspy, 2009b). Alarmingly, a growing number of studies have demonstrated that ESA-based treatment can compromise overall survival of cancer patients (Crouch and DeSantis, 2009; Kumar et al, 2012; Tovari et al, 2008; Wang et al, 2011), raising the possibility of growth-stimulatory effects on cancer cells via the canonical Epo receptor (EpoR) (Aapro et al, 2012; Chateauvieux et al, 2011; Hedley et al, 2011; McKinney and Arcasoy, 2011; Rathod and Salahudeen, 2011). However, EpoR expression on cancer cells has largely failed to explain the effects of rhEpo on tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Epo is a pleiotropic cytokine that regulates erythropoiesis, angiogenesis, cytoprotection, and proliferation (Foley, 2008; Glaspy, 2009b). Alarmingly, a growing number of studies have demonstrated that ESA-based treatment can compromise overall survival of cancer patients (Crouch and DeSantis, 2009; Kumar et al, 2012; Tovari et al, 2008; Wang et al, 2011), raising the possibility of growth-stimulatory effects on cancer cells via the canonical Epo receptor (EpoR) (Aapro et al, 2012; Chateauvieux et al, 2011; Hedley et al, 2011; McKinney and Arcasoy, 2011; Rathod and Salahudeen, 2011). However, EpoR expression on cancer cells has largely failed to explain the effects of rhEpo on tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional role of EPO in tumor biology is still far from being fully understood. In spite of a growing amount of in vitro and in vivo studies (Shi et al 2010;Kumar et al 2011) that associate the presence of EpoR with the promotion of cancer cells proliferation and invasion, a linear correlation between EpoR activation and an efficient responsiveness to exogenous EPO administration has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…The WM35 cell line was originally derived from a melanoma lesion at the Radial Growth Phase when presumably most of the melanoma cells have not acquired the ability to form metastases, while the A2058 cell line was derived from a metastatic lymph node36. A striking difference between WM35 and A2058 cell lines is that the former does not form tumors in xenograft models in mice, while the latter is capable of growing tumors in an immune-compromised mouse model3738. Furthermore, previous studies from our group have characterized these melanoma cell lines based on cell invasiveness and adhesiveness and found that these characteristics correlate with metastatic potential39.…”
Section: Resultsmentioning
confidence: 99%